2019
DOI: 10.1016/j.jobcr.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of Moxifloxacin Hydrochloride loaded in-situ gel for the treatment of periodontitis: In-vitro drug release study and antibacterial activity

Abstract: Periodontitis is one of the most widespread oral diseases. Medicated in-situ gels of Moxifloxacin Hydrochloride for extended period of retention in infected cavity were prepared for improved local action for the treatment of periodontitis. Medicated formulations were prepared using temperature sensitive (poloxamer 407), ion sensitive (gellan gum) and pH sensitive (carbopol 934P) polymers. 32 Full Factorial Design has been applied and prepared batches were characterized by FTIR, pH, syringeability, drug content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 13 publications
3
44
0
Order By: Relevance
“…In this study, the cold method was applied for the preparation of the thermosensitive in situ gels of THZ. Besides, there are also other methods as the hot process which, however, leads to undesirable physiochemical effects as the formation of polymeric lumps (Swain, Patel, Gandhi, & Shah, 2019). There are various polymers which are used for the preparation of the in situ gels, either natural or synthetic (Güven, Berkman, Şenel, & Yazan, 2019; Üstündağ Okur et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the cold method was applied for the preparation of the thermosensitive in situ gels of THZ. Besides, there are also other methods as the hot process which, however, leads to undesirable physiochemical effects as the formation of polymeric lumps (Swain, Patel, Gandhi, & Shah, 2019). There are various polymers which are used for the preparation of the in situ gels, either natural or synthetic (Güven, Berkman, Şenel, & Yazan, 2019; Üstündağ Okur et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the table, the hardness value of the gels increased significantly as the PLX 407 ratio increased. Similarly, Swain et al expressed that the hardness of the formulation increases as the concentration of polymer increases for their in situ gel formulations [35]. Although the hardness value was increased, it was observed that this value did not adversely affect the application and spreading of the formulation.…”
Section: Determination Of Mechanical Propertiesmentioning
confidence: 97%
“…Recently, in situ gel formulation for local delivery moxifloxacin hydrochloride in periodontal disease has been developed by Swain et al [ 95 ]. The gel formulations were prepared using thermally-sensitive (Poloxamer 407), ion-sensitive (Gellan gum), and pH-sensitive (Carbopol 934P) polymers.…”
Section: Hydrogelsmentioning
confidence: 99%